Religious Education in Russian Schools: Plans, Pains, Practices - Olga A. Iakimova; Andrey S. Menshikov (Changing Societies & Personalities, 2020)
Since 2012 the compulsory course “Fundamentals of Religious Cultures and Secular Ethics” has been taught in all public schools of Russia. The introduction of the course compelled Russian scholars to engage in comparative research on the development of normative framework and teaching practice in religious education. Despite the importance of global trends and international debates, it is crucial to observe the local dynamics and discover how particular conceptualizations of religion, education goals, principles and teaching practices affect religious education and its development. In our research, we focus on the case of religious education in Sverdlovsk region with the view to discover how successful are the plans which originated in the efforts of the Russian Orthodox Church to gain entry to public schools, but were moderated by the resistance of educational and academic community. How effective are the practices? What unforeseen issues transpired in its implementation? Intending to highlight some major characteristics of the emerging model of religious education in Russian Federation we conducted a set of semi-structured interviews with the representatives of major groups involved in teaching (public authorities; established religious organizations; education officials; educators; parents whose children attend the course modules and, finally, academic community in Religious Studies) and on its basis we conclude that religious education at Russian schools today rests on a discrepancy between the alleged goals of the course “Fundamentals of Religious Cultures and Secular Ethics”, which emphasize multicultural education, and its implementation, which stems from practical constraints and local agendas.